A STUDY ON KANDUGHNA TAILA IN FILARIAL LYMPHANGITIS AND ULCERS - Prasad, Goli Penchala; Swamy, G.K.; Naidu, M. L. (International Journal of Ayurveda and Pharma Research, 2015)
The disease Shlipada is very common in Andhra Pradesh Coastal belts. The chronic filarial patients used to suffer from acute periodic episodes. During these acute periodic episodes majority of the filarial patients develop lymphangitis (inflammation of lymphatic vessel), wounds and ulcers in affected legs. Some of the patients develop oozing blisters and pustules. Patients with these acute symptoms suffer from severe pain and tenderness and un-hygiene may lead to secondary bacterial infections. These periodic episodes often end with fibrosis and permanent swelling (Lymphedema). Many Ayurvedic herbal and herbo-mineral drugs were successfully used internally to reduce chronic filarial swelling (lymphedema), but there is an ultimate need to find an external application to reduce the acute symptoms like lymphangitis, wounds and ulcers. Kandughna taila is a Ayurvedic herbal oil prepared from Kandughna Dashaimani (a group of 10 drugs indicated in Itching) of Caraka samhita. This Kandughna taila was selected to study externally on Filarial patients. As a part of PhD study to find the efficacy of drug this oil alone was used in 28 patients in an open clinical trail. Encouraging results were observed during and after 30 days of treatment. Out of 28 cases, 8 (28.8%) got good response, 15 (53.6%) got fair response, 2 (7.1%) got poor response and 3 (10.7%) cases did not show any response. Overall 63.68% relief was found in all acute clinical parameters. Parameter wise 62% of relief in lymphangitis, 56.1% in pain, 62.5% in tenderness, 77.78% relief in wound/ ulcer were found. In statistical analysis based paired t-test relief on acute symptoms like lymphangitis, pain, tenderness, wound were found highly significant (P<0.0001). Statistically overall effect of treatment on acute symptoms was also found highly significant (P<0.0001).